Emerging radiation techniques for early-stage breast cancer after breast-conserving surgery. (July 2011) - Lyons, Janice A; Woods, Charles; Galanopoulos, Nicholas; Silverman, Paula
Standard whole-breast irradiation consisting of a dose of 45–50 Gy over 5 weeks with or without the addition of a boost to the tumor bed has equivalent survival to mastectomy and is considered to be the standard of care for most patients with early-stage breast cancer. Newer techniques have been developed to shorten the course of radiation or limit normal tissue exposure in an attempt to increase accessibility to and tolerance of radiation therapy. This article will review some of the newer regimens and techniques for treating early-stage breast cancer after breast-conserving surgery.